THE NATURE OF MASKELYNITE IN SHOCKED METEORITES: NOT DIAPLECTIC GLASS BUT A GLASS QUENCHED FROM SHOCK-INDUCED DENSE MELT AT HIGH PRESSURES - Chen M.; El Goresy A. (My University, 2000)
Maskelynite, an important constituent of shocked meteorites, once thought to be diaplectic plagioclase glass formed by shock-induced solid-state transformation. Our systematic investigation of shocked L-chondrites and SNC meteorites indicates that maskelynite does not contain inherited fractures or cleavage, and shock-induced fractures. We found no evidence for models calling for melting that initiated in PDFs and affected the whole crystals. Maskelynite grains are smooth and display radiating cracks emerging from their surfaces into neighboring pyroxene. This is indicative of shock-induced melting and quenching of the dense melt at high pressure, thus erasing the inherited and shock-induced fractures. This was followed by relaxation of the dense plagioclase glass, which induced the expansion cracks in pyroxene and olivine. Enrichment in potassium, deviation from stoichiometry, degradation of igneous zoning, the presence of offshoots of maskelynite in pyroxene, the lack of vesiculation in the melt pockets, melt veins and molten mesostasis are clear evidence for melting and quenching under high pressure. Our investigations present unequivocal evidence that maskelynite in meteorites is not diaplectic plagioclase glass formed by solid-state transformation, but a dense quenched glass. The duration of the shock pulse in natural events can be several orders of magnitude longer than in shock experiments. Since kinetic effects are crucial factors in promoting phase transitions, vitrification and melting, experimentally induced solid-state vitrification of plagioclase produced in dynamic experiments is inadequate for calibration of peak shock pressures in maskelynite-bearing natural samples.
Keywords: MASKELYNITE; MELTS; GLASSES; L CHONDRITES; SNC METEORITE